Natural aerosol–climate feedbacks suppressed by anthropogenic aerosol. Issue 19 (15th October 2013) - Spracklen, D. V.; Rap, A.
Abstract [1] The natural environment is an important source of atmospheric aerosol such as dust, sea spray, and wildfire smoke. Climate controls many of these natural aerosol sources, which, in turn, can alter climate through changing the properties of clouds and the Earth's radiative balance. However, the Earth's atmosphere is now heavily modified by anthropogenic pollution aerosol, but how this pollution may alter these natural aerosol–climate feedbacks has not been previously explored. Here we use a global aerosol microphysics model to analyze how anthropogenic aerosol alters one link within these feedbacks, namely, the sensitivity of cloud albedo to changes in natural aerosol. We demonstrate that anthropogenic aerosol in the Northern Hemisphere has halved the hemispheric mean cloud albedo radiative effect that occurs due to changes in natural aerosol emissions. Such a suppression has not occurred in the more pristine Southern Hemisphere.